0.18µm-CMOS Rectifier with Boost-converter and Duty-cycle-control for Energy Harvesting - Roskhatijah Radzuan; Mohd Khairul Mohd Salleh; Nuha A. Rhaffor; Shukri Korakkottil Kunhi Mohd (Institute of Advanced Engineering and Science, 2018)
Existing works on battery-less of energy harvesting systems often assume as a high efficiency of rectifier circuit for power management system. In practice, rectifier circuit often varies with output power and circuit complexity. In this paper, based on a review of existing rectifier circuits for the energy harvesters in the literature, an integrated rectifier with boost converter for output power enhancement and complexity reduction of power management system is implemented through 0.18-micron CMOS process. Based on this topology and technology, low threshold-voltage of MOSFETs is used instead of diodes in order to reduce the power losses of the integrated rectifier circuit. Besides, a single switch with the duty-cycle control is introduced to reduce the complexities of the integrated boost converter. Measurement results show that the realistic performances of the rectifier circuit could be considerably improved based on the performances showed by the existing study.